Electric field analysis of water droplet deformation on solid insulation surface using finite element method - Zulkifli, Nurina (Universiti Sains Malaysia, 2017)
In this paper, a two-dimensional composite polymer insulator was model to study the electric field distribution on the insulator surface in the influence of water droplet deformation with different contact angle and to analyze the effect of insulator material with and without alumina nanofiller with different loading concentration. It was simulated using the finite element software (FEM) named Comsol Multiphysics 5.a version. This method of analysis followed the standard of surface tracking and erosion which is IEC 60587. Parameters that were used in this simulation were the contact angle of the water droplet and the relative permittivity of the SiR/EPDM with and without nano-filler. The loading concentration of nanofiller used were 1 Vol % and 2 Vol % and the contact angle of water droplet were varies at 30°,60°,90° and 120°. The results showed that there were electric field intensification at the interface between the surface of water droplet, insulator surface and air. The electric field distribution changed from high to low in value from hydrophilic to hydrophobic state. The addition of nanofiller reduced the magnitude of the electric field. The relationship of the electrical field distribution and all of these parameters were figured out. These relationship were studied by plotting the graph of electrical field distribution versus all of these parameters used.